The different effects of substrates and nucleotides on the complex formation of ABC transporters - Fiorentino, F; Bolla, J; Mehmood, S; Robinson, C (Elsevier, 2019)
The molybdate importer (ModBC-A of Archaeoglobus fulgidus) and the vitamin B12 importer (BtuCD-F of Escherichia coli) are members of the type I and type II ABC importer families. Here we study the influence of substrate and nucleotide binding on complex formation and stability. Using native mass spectrometry we show that the interaction between the periplasmic substrate-binding protein (SBP) ModA and the transporter ModBC is dependent upon binding of molybdate. By contrast, vitamin B12 disrupts interactions between the transporter BtuCD and the SBP BtuF. Moreover, while ATP binds cooperatively to BtuCD-F, and acts synergistically with vitamin B12 to destabilize the BtuCD-F complex, no effect is observed for ATP binding on the stability of ModBC-A. These observations not only highlight the ability of mass spectrometry to capture these importer-SBP complexes but allow us to add molecular detail to proposed transport mechanisms.